Bodyblade™ Training in Athletes with Traumatic Anterior Shoulder Instability - Victor Pulido; Brent Alvar; David Behm (North American Sports Medicine Institute, 2023)
# Background The Bodyblade™ has the potential of enhancing conservative management of Traumatic Anterior Shoulder Instability (TASI). # Purpose The purpose of this study was to compare three different protocols: Traditional, Bodyblade™, and Mixed (Traditional & Bodyblade™) for shoulder rehabilitation on athletes with TASI. # Study Design Randomized-controlled longitudinal training study. # Methods Thirty-seven athletes (age = 19.9±2.0 years) were allocated into Traditional, Bodyblade™, and Mixed (Traditional/Bodyblade™) training groups (3×week for 8-weeks). The traditional group used resistance bands (10-15 repetitions). The Bodyblade™ group transitioned from classic to the pro model (30-60-s repetitions). The mixed group converted from the traditional (weeks 1-4) to the Bodyblade™ (weeks 5-8) protocol. Western Ontario Shoulder Index (WOSI) and the UQYBT were evaluated at baseline, mid-test, post-test, and at a three-month follow-up. A repeated-measures ANOVA design evaluated within and between-group differences. # Results All three groups significantly (p=0.001, eta^2^: 0.496) exceeded WOSI baseline scores (at all timepoints) with training (Traditional: 45.6%, 59.4%, and 59.7%, Bodyblade™: 26.6%, 56.5%, and 58.4%, Mixed: 35.9%, 43.3% and 50.4% respectively). Additionally, there was a significant (p=0.001, eta^2^: 0.607) effect for time with mid-test, post-test and follow-up exceeding baseline scores by 35.2%, 53.2% and 43.7%, respectively. The Traditional and Bodyblade™ groups (p=0.049, eta^2^: 0.130) exceeded the Mixed group UQYBT at post-test (8.4%) and at three-month follow-up (19.6%). A main effect (p=0.03, eta^2^: 0.241) for time indicated that WOSI mid-test, post-test and follow-up exceeded the baseline scores by 4.3%, 6.3% and 5.3%. # Conclusions All three training groups improved their scores on the WOSI. The Traditional and Bodyblade™ groups demonstrated significant improvements in UQYBT inferolateral reach scores at post-test and three-month follow-up compared to the Mixed group. These findings could lend further credibility to the role of the Bodyblade as an early to intermediate rehabilitation tool. # LEVEL OF EVIDENCE 3